ON THE PROBLEM OF USING NATURAL BIOLOGICALLY ACTIVE SUBSTANCES TO ACTIVATE ARTEMIA EGGS - UbaskinА. V.,; Tarasovskaya N. E.,; Akhmetov K. I.,; Lunkov A. I., (Academic Journal of Physical and Chemical Sciences, 2020)
Currently branchiopod from the genus of Artemia Leach, 1819 became the common starting feed №1 for growing young aquatic organisms. However, there is often reduced hatching of nauplius from the collected eggs and artificial activation is required. As a result of empirical research, it was possible to experimentally detect the activating effect of excretion products – diluted adult urine. The research was carried out in several stages. It was found that the rate of germination growth for different populations ranges from 0, 2 to 0, 6% per day. In the first experiment, cysts with 24% of hatching were placed in a solution of lake water diluted with urine to a concentration of 105 g/l. After two weeks, the outage reached 66. 7 % and exceeded the control 2.55 times. But over time, the activity of the embryos decreased and by the end of April, the hatching reached zero. By using eggs from the 1st experiment with 66. 9% hatching in a fresh solution of «lake water + urine» (105 g / l) on the first day, the hatching exceeded the control by 52. 1% and by 23.7% the data from experiment 1.Later, when 80.8% were hatched, a large number of weakened and dead nauplius was observed. In the third experiment, spring egg with a hatching rate of 36. 7% was used. Different salinity concentrations (110-140 g/l) were used due to dilution of lake water (233 g/l) with urine and fresh water. When activated in a solution with a salinity of 110 g/l after one month, the discharge exceeded the control by 1. 65 times. At the end of the experiments, an increase in the salt concentration reduced the activating effect with a slight decrease in hatching. The mechanisms of activating action of the components of the proposed liquid folds the physiological effects of steroid hormone metabolites on the formation of the larva in the egg and the destructive physical and chemical effects of a number of substances on the egg shell. For complex activation of the development of the embryo with the destruction of egg’s shells, savings are achieved in the plastic and energy substances available in the egg, preserving the nutritional value of nauplius.